OSDs and knowledge: evolutions in a Development Bank - Queirós , Juliana Clyde Fernandes Ferreira de (Technical and Scientific Journal Green Cities, 2025)
The present work sought to analyze variables related to the OSDs of a Development Bank, between the years 2015 and 2023, in order to correlate financing and internal activities developed related to the theme, assuming that there would be a significant correlation between these variables as suggested by Nonaka and Takeuchi (2024) regarding knowledge exchange. The hypotheses were partially accepted because it was possible to verify that there was a significant correlation in part of the financing and actions. It was found that the hypotheses were null for the variables customer satisfaction and Female Succession. The work sought to contribute to the study of the evolution of the SDGs in financial institutions and, in particular, in development banks.